Microencapsulated and uncoated butyric acid as alternative additives to the regeneration of intestinal mucosa in broilers challenged with Eimeria spp. - Ventura, G. [UNESP]; Lima, G. A. [UNESP]; Barbosa, B. F.S. [UNESP]; Polycarpo, G. V. [UNESP]; Denadai, J. C. [UNESP]; Costa, V. E. [UNESP]; Madeira, A. M.B.N.; Malheiros, R. D.; Cruz-Polycarpo, V. C. [UNESP] (Taylor & Francis, 2021)
1. The effect of microencapsulated and uncoated butyric acid as an alternative to antibiotics on performance, intestinal morphology and regeneration of intestinal mucosa was studied in birds experimentally infected with Eimeria spp. 1 to 42 d-old. 2. A total of 1,320 male Cobb® broiler chicks were allocated to one of five treatments in a completely randomised design, comprising a negative control, uncoated butyric acid (UA), microencapsulated butyric acid (MA), combined U + M butyric acid and a positive control (antibiotic+anticoccidial) in six replications. At 16 d-old, the birds were inoculated orally with 0.5 ml of a solution containing an Eimeria spp. pool. 3. At 21 d of age, the birds receiving butyric acid alone had higher body weight gain (BWG) and feed intake (FI) compared to those supplemented with the blend of acids. For the total rearing period, in all variables, the positive control performed best (P < 0.001). 4. At 14 d of age, birds that received diets containing UA had a deeper crypt depth in the jejunum than those fed diets containing microencapsulated acid (P = 0.0194). At 21 d of age, the birds fed the acids had higher villi (P = 0.0058) in the duodenum, compared to the negative control group. 5. Supplementation with microencapsulated acid contributed to the intestinal health and recovery of post-challenge birds, but did not result in improvements in performance.
Keywords: Carbon-13; Eimeria spp; intestinal morphology; microencapsulation; oocyst; regeneration; sodium butyrate; stable isotope